ChatGPT: a New Tool to Improve Teaching and Evaluation of Second and Foreign Languages a Review of ChatGPT: the Future of Education - Zanyar Nathir Ghafar (International Journal of Applied Research and Sustainable Sciences, 2023)
Concerns about the future of education have been amplified in recent years as a result of the introduction of the innovative online application ChatGPT. Because they depend so much on written assessments, teachers of foreign languages experienced increased levels of worry, which were further made worse by the extensive publicity the topic received in the media.The current topic is centered on the significant debate that has taken place regarding the highly idealized capabilities of the chatbot. Therefore, the first thing that is going to be done in this article is to provide a complete explanation of the mechanics, functions, and common misconceptions about ChatGPT. This review paper aims to focus on positives and negatives that are associated with the employment of chatbots are the first topic that is investigated in this research. After that, a thorough investigation into the ways in which students and teachers may most efficiently make use of the chatbot is carried out. Some people believe that ChatGPT offers substantial opportunities for teachers and educational institutions to improve the ways in which they teach and evaluate second and foreign languages. In addition to this, it has provided academics with a number of new research paths to investigate, most notably in the field of customized education.